IMPROVING STUDENTS ABILITY IN WRITING REPORT TEXT THROUGH PEER RESPONSE TECHNIQUE - Sriwiyanti, Agus; Apriliaswati, Rahayu; ., Sumarni (Jurnal Pendidikan dan Pembelajaran Khatulistiwa, 2013)
Abstract: This study was a classroom action research (CAR) to improve students writing ability on report text in senior high school students. In this study, Peer Response Technique was used as a strategy to help students in writing report text. The process of Peer Response Technique consists of revising activity which helped the students to write the generic structure of report text such as general classification and identification and editing activity that helped the students to write the language features of report text by checking the use of vocabulary and grammar. The techniques of data collecting in this research were observation checklist, field note, and writing test. Data was analyzed by using scoring profile. The students writing ability in report text improved in three cycles from 55.86 in cycle 1 then improved to 61.89 in cycle 2 and up to 68.73 in cycle 3. The improvements of this study were particularly in students writing on generic structure and language features of report text. Keywords: writing ability, peer response technique, classroom action research, report text. Abstrak: Penelitian ini adalah penelitian tindakan kelas (CAR) yang bertujuan untuk meningkatkan siswa dalam menulis sebuah teks report pada siswa sekolah menengah atas. Dalam penelitian ini, tehnik Peer Response digunakan sebagai strategi untuk membantu siswa dalam menulis teks report. Tehnik Peer Response terdiri dari aktivitas merevisi yang membantu siswa dalam menulis bentuk umum dari sebuah teks report seperti mengklasifikasikan dan mendeskripsikan sebuah topik dan editing untuk membantu siswa dalam menulis ciri kebahasaan dari sebuah teks report dengan memeriksa kembali penggunaan kosa kata dan gaya bahasa di dalam teks. Tehnik pengumpulan data yang digunakan meliputi lembar observasi, catatan lapangan, dan tes menulis. Hasil data penelitian dianalisis berdasarkan rubrik penilaian. Kemampuan siswa dalam menulis teks report mengalami peningkatan pada tiga siklus dari 55,86 pada siklus pertama kemudian meningkat menjadi 61,89 pada siklus kedua dan mencapai 68,73 pada siklus ketiga. Peningkatan yang dialami siswa dalam penelitian ini umumnya pada kemampuan menulis bentuk umum dan ciri kebahasaan dari teks report. Kata kunci: kemampuan menulis, tehnik peer response, penelitian tindakan kelas, teks report